Research in intelligent medical system: Problems and solution - Wan Ishak, Wan Hussain; Siraj, Fadzilah; Othman, Abu Talib (2002)
Advancement in computer systems could assist the doctors to make decision without direct consultation with the specialist. Medical information systems were developed in most hospital or health care provider to manage patients' recordr and enhance the current practice of medical records. A computer program known as Medical Decision-Support System was designed to help health professionals to make clinical decision (Shortliffe,1987). The system deals with medical data or with the knowledge of medicine to help in determining the nature ofthe patient's disease to diagnosis or administer therapy. However, developing medical system, especially intelligent medical system could be a dificult task. This paper discusses the experience of doing research in medical domain. The problems encounter and the solutions for future work are presented.